The impact of interactive social media advertising on brand resonance in South Africa - Qutywa, Pinda (My University, 2020)
Interactive Social Media advertising offers our population many benefits, whether it be entertainment, news, education, customer service or even networking. Social media is changing the rules of branding. Brands can be noticed with smaller investments as they can tap into social media to amplify their brand message. The ever-evolving impact of social media on branding is shifting the very essence of brand management. Social media binds together communities that once were geographically isolated. Insights from various social networks enable marketers to understand what customers want, and when they want it, how they want to experience it and who they want to experience it with, all of which will enable messaging that they want to hear. On the World Wide Web, the brand is the experience and the experience is the brand. Although branding has been a subject of research for many years, the subject of social media is new and emerging, therefore the scope of research has widened, creating opportunities to expand on existing knowledge and theory. Largely, research specific to brand advertising and brand resonance has not incorporated social media particularly in the emerging market context such as South Africa. There is a lack of academic research revealing how social media, advertising and brand resonance interconnect in the South African skincare market context. The purpose of this study was to investigate influence of social media advertising interactivity on brand resonance. The brand resonance construct is measured from the perspective of its four dimensions namely, loyalty, attachment, community and engagement. An online survey was administered to 3,000 respondents. Out of that, 1959 completed the survey in full. The respondents were regular users of social network sites and they were sourced mainly from university students, a smaller percentage of the group consisted of university staff and other members of the public. Data was analyzed using the R-software version 3.6.3, to determine if the items correlate with their unique constructs. The conceptual model elements were analyzed using exploratory factor analysis. The study showed that interactive social media advertising has a positive and significant impact on brand loyalty, brand attachment, brand community and brand engagement. The study gives marketers insights into how to effectively use social media as an advertising medium, but most importantly how to use social media to create brand resonance.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Brand; Brand Knowledge and related constructs of Brand Awareness and Brand Image; Brand Resonance and its related constructs i.e. Brand Loyalty; Brandb Attachment; Brand Community; Brand Relationship; Social Media; SDG-8: Decent work and economic growth